EXPERIMENTAL STUDY ON J-INTEGRAL VALUE FOR THREE-POINT BEND SPECIMEN - SU HongYing; LIU RenDong; LI WenZhu; LIN Li; XU Xin (Jixie qiangdu)
Using two different kinds of three-point bend specimens,J-integral values calculated based on plastic area of under load-notch-opening displacement curve, according to GB/T 21143-2014 and GB/T 21143-2007, GB/T 2358-1994 appendix D two standards,combining with the two different methods to calculate the J-integral values. The results showed that with respect to the different crack extension △a,J-integral values from low to high values,the average relative deviation of two methods J-integral value < 2. 0%,illustrated with GB/T 21143-2007,GB/T 2358-1994 Appendix D combined two standards can also accurately calculate the J-integral values,a method of calculating the J-integral values using a three-point bending specimen was provided.